Non-linguistic Context Indication in The Holy Quran - محمّد عليّ الأرناؤوطيّ, إياد (Al-Adab Journal, 2018)
The Holy Quran forms a system that its parts uphold and not contradict each other . This can be applied to it throughout two contexts : Linguistic and non-linguistic, just like the other speech .But ,its structure has certain characteristics unlike the other structuresThe linguistic context of The Holy Quran implies several contexts regarding to what is in or out the text like: occasion context which is almost represented in descend reason . Descend reasons are "things that had happened during the Message(Risala) time and needed the descend of revelation (Wahi) as a resultAfter my following up the (Mizan ) Interpretation , I discovered that the interpreter supported his interpretation ,for the verse in its linguistic context, with descend reasons narration and when they contradict to each other , the interpreter presented the linguistic context indication (narration of descend reason) .But , the interpreter benefited from constant citingThere are advantages for the reasons of descend like;To say in a certain meaning and abandoning the other one (probable in the context)in addition to outlining a vague matter in the context.